Equity analysis of bus network balance from the perspective of spatial morphology and service capability - Hui Li; Chao Chen; Ying Yuan; Xiaohui Xia; Qianye Huang; Lianhong Ye; Zongcai Huang (Scientific Reports)
Abstract A balanced and equitable bus network layout plays a crucial role in the efficient operation of cities. The layout of urban bus networks is influenced by various factors, including urban planning, population size, industrial distribution, and road network layout. Forming a comprehensive indicator system and analyzing the balance and fairness of bus network layouts are key research areas. This paper proposes a framework for quantitatively analyzing the balance and fairness of bus network services from the perspective of bus route service capacity (the maximum passenger transport capacity, the number of bus routes available for transfer, resource allocation), considering the spatial characteristics of urban road networks and surrounding facilities, and utilizing methods such as spatial accessibility and space syntax. A comprehensive index for quantitatively measuring bus routes was constructed. The results show that the comprehensive index values of Xiamen bus routes decrease from the inner island to the outer areas, reflecting a relatively balanced bus network layout in Xiamen. Combining the comprehensive index with various influencing factors, bus routes with high service fairness are characterized by concentrated layouts and dense nearby populations, while routes with scattered layouts and sparse nearby populations exhibit low service fairness. The research results provide fundamental data, theoretical and technical support for analyzing the balance and fairness of the bus network layout in Xiamen.